Investigating the hybrid nature and the sheer variety of virtual thefts (A critique of the general comment on Articles 12 and 13 related to Cybercrimes and Computer crimes) - Aliakbar Izadifard; Seyed Mojtaba Hoseinnejad (مطالعات فقه و حقوق اسلامی, 2019)
The tremendous technological advances following the entering into virtual arena have increased the number of incidents of various crimes, especially virtual thefts. The purpose of this study was to investigate the sheer variety and hybrid nature of virtual thefts, compare it with that of traditional form, review some pieces of problems and try to solve them and also prove the compatibility of virtual theft with traditional one correspondences for subjecting the perpetrator to Hadd punishment. After comparing the traditional thefts with those of virtual ones including virtual embezzlement, the authors arrived at the conclusion that there is a need to review the articles 12 and 13 concerning the cybercrime and computer crime law.